1998
DOI: 10.1002/(sici)1098-2264(199805)22:1<16::aid-gcc3>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic analysis of 46 pleomorphic soft tissue sarcomas and correlation with morphologic and clinical features: A report of the CHAMP study group

Abstract: With the aim of identifying objective cytogenetic‐morphologic correlations, we evaluated 46 pleomorphic soft tissue sarcomas (mainly diagnosed originally as malignant fibrous histiocytomas) with clonal chromosome aberrations both cytogenetically and morphologically as part of an international collaborative study. By detailed histopathologic examination, most cases could be categorized into specific tumor types. Eight sarcomas were diagnosed as lipogenic (4 pleomorphic, 1 combined pleomorphic and myxoid/round c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
93
2
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(101 citation statements)
references
References 18 publications
5
93
2
1
Order By: Relevance
“…In contrast to the highly complex and inconsistent karyotypes obtained by chromosomal banding analysis 6,13 and to one recurrent chromosomal abnormality detected with CGH in a small number of pleomorphic LS analyzed by Parente et al, 22 we identified in our series of pleomorphic LS analyzed by CGH a considerable number of recurrent chromosomal imbalances. Moreover, our data show that the DNA copy number changes detected in pleomorphic LS differ essentially from those in the cytomorphologically similar high-grade areas of dedifferentiated LS and from those in well-differentiated LS/ALT described in the literature.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…In contrast to the highly complex and inconsistent karyotypes obtained by chromosomal banding analysis 6,13 and to one recurrent chromosomal abnormality detected with CGH in a small number of pleomorphic LS analyzed by Parente et al, 22 we identified in our series of pleomorphic LS analyzed by CGH a considerable number of recurrent chromosomal imbalances. Moreover, our data show that the DNA copy number changes detected in pleomorphic LS differ essentially from those in the cytomorphologically similar high-grade areas of dedifferentiated LS and from those in well-differentiated LS/ALT described in the literature.…”
Section: Discussioncontrasting
confidence: 92%
“…6,13 Except for the presence of definite evidence of adipocytic differentiation, pleomorphic LS are histomorphologically often similar to pleomorphic malignant fibrous histiocytomas (MFH) or MFH-like pleomorphic tumors with different lines of cellular differentiation; additionally, an epithelioid variant of pleomorphic LS focally resembling a solid carcinoma has been described. 2 Although the high-grade component of dedifferentiated LS, which may be predominating especially in tumor recurrences, is frequently MFHlike, dedifferentiated LS differ irrespective of the grade of the non-lipogenic component from pleomorphic LS by a less aggressive biological behavior.…”
mentioning
confidence: 99%
“…Most reported karyotypes are complex, contain a high number of chromosomal changes, and show marked heterogeneity within this group of sarcomas. [14][15][16][17][18][19] Comparative genomic hybridization (CGH) studies have also shown multiple and complex changes, suggesting a genetically advanced disease. So far, CGH has been used to identify gains and losses of DNA copy number changes in less than 200 cases of leiomyosarcoma.…”
mentioning
confidence: 99%
“…One might also hope that each of the pleomorphic sarcomas would harbor a unique cytogenetic abnormalities that would allow each to be studied and understood more mechanistically, as has occurred with many of the nonpleomorphic sarcomas, such as myxoid liposarcoma, Ewing's sarcoma, alveolar rhabdomyosarcoma, and clear cell sarcoma. To date, no recurring specific differences have been noted among pleomorphic sarcomas (41). All are characterized by numerous and complex genetic alterations (Fig.…”
mentioning
confidence: 99%
“…All are characterized by numerous and complex genetic alterations (Fig. 19), although there appears to be a correlation between the degree of complexity and the grade (41). One exception is the dedifferentiated liposarcoma, which retains giant marker and/or ring chromosomes as a vestige of its origin from a welldifferentiated liposarcoma (42) (Fig.…”
mentioning
confidence: 99%